Integration of Blockchain Technology in Secure Data Engineering Workflows - Pradhan, Chittaranjan; Trehan, Abhishek (International Journal of Computer Sciences and Engineering, 2025)
A major step forward in guaranteeing data integrity, into safe data engineering processes. The immutability and decentralization of blockchain ledgers make it an ideal solution for problems including data provenance, access control, and tamper resistance. Examining blockchain`s potential in safe data processes, this research highlights the technology`s ability to facilitate real-time data exchange, strengthen audit trails, and improve compliance with regulatory requirements. Some important use cases include distributed system data sharing in a safe environment, smart contract-based simplified access control, and immutable tracking of data modifications. New approaches, such as hybrid blockchain models and layer-two scaling methodologies, are being considered as potential answers to existing problems, including scalability, integration complexity, and energy efficiency. The results show that blockchain technology, when used correctly, may make data processes more trustworthy and resilient, giving businesses an advantage when it comes to handling important and sensitive data. To highlight blockchain`s revolutionary potential in safe data ecosystems, this article finishes with suggestions for applying blockchain-based solutions to data engineering techniques. Blockchain technology offers a fresh perspective on data quality, security, and transparency issues when integrated into safe data engineering procedures. The distributed and immutable ledger technology known as blockchain provides a solid basis for building confidence in data-driven procedures. Data provenance, safe sharing, and auditability are three important topics that this study focusses on as it analyses the potential of blockchain in improving secure data operations. Blockchain technology allows distributed systems to have automatic validation and safe interactions by using smart contracts and cryptographic approaches. According to the results, using blockchain technology improves data security and boosts operational efficiency by cutting out middlemen. But there are obstacles that must be carefully considered, including compatibility, adoption costs, and scalability. The paper finishes with some suggestions for how data engineering processes might make the most of blockchain technology, which has the ability to revolutionize data management methods and guarantee compliance and security in contemporary ecosystems.